Qasr Mushash-Survey, Jordanien: Die Arbeiten der Jahre 2012 und 2013 - Bartl, Karin (e-Forschungsberichte des DAI, 2023)
Qasr Mushash is among the so-called desert castles, which can be regarded as the most characteristic group of monuments of early Islamic times, particularly the Umayyad period (630‒750 AD), in the Levant and its hinterland. The different structures of the desert castles indicate a wide variety of functions, which includes temporarily occupied residences of elites, smaller settlements or caravan stations along trade routes. Qasr Mushash with its numerous water installations might be one of the latter type. The Qasr Mushash Survey provides detailed examinations of the building structures and water management.